Antibacterial activity of marine bacteria associated with sponges from Phu Quoc island in Vietnam - Trinh, Phan Thi Hoai; Ngoc, Ngo Thi Duy; Tien, Phi Quyet; Hung, Le Dinh; Trang, Vo Thi Dieu; Hang, Cao Thi Thuy; Khanh, Huynh Hoang Nhu; Van, Tran Thi Thanh; Ly, Bui Minh (Vietnam Journal of Biotechnology, 2016)
Sponge associated marine microbes recognised as potential candidate for screening and isolation of bioactive compounds. In this work, thirty-one marine bacterial strains associated with seven species of sponges collected from Phu Quoc Island, Vietnam were isolated and screened for antimicrobial activity against selected human and animal pathogens including Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Vibrio parahaemolyticus, Vibrio harveyi, Bacillus cereus, Streptococcus faecalis, Listeria monocytogenes, Proteus mirabilis and Klebsiella pneumoniae using agar well diffusion assay. Twenty-six percent of bacterial strains were found to be antibacterial producers and their activities ranged from broad spectral to species specific (P. aeruginosa, E. coli, P. mirabilis, B. cereus, and L. monocytogenes). Out of the 31 marine bacterial strains subjected to preliminary screening for antibacterial activity, 8 isolates exhibited antibacterial activity against at least two tested pathogens, that 55% against P. mirabilis, 22% against P. aeruginosa, 10% against E. coli and 6% against K. pneumoniae, B. cereus and L. monocytogenes. A strain coded 045-203-4 was found to be highly potent and was cultured for further study. The strain produced metabolites with good activity in medium contained yeast extract (0.8% w/v), glucose (0.5%) at pH 7.0 and after incubated shaking for 30 h at 150 rpm. In addition, strain 045-203-4 was analyzed for morphological and physiological characteristics. Analysis of the nucleotide sequence of 16s rRNA gene of strain 045-203-4 showed a strong similarity (99%) with that of the 16s rRNA gene of Bacillus subtilis. The present investigation reveals that the marine bacteria isolated from sponges at Phu Quoc Island can be a definite source for novel antibiotics.